Influence of planting methods, spacing and farmyard manure on growth, yield and nutrient content of turmeric (Curcuma longa L.) - Saini, B S Gill, Simerjit Kaur, S S (Journal of Spices and Aromatic Crops, 2004)
Investigations carried out at Ludhiana (Punjab), with different methods of planting (flat and ridge), spacings (60 em x 10 cm and 60 cm x 15 cm) and farmyard manure levels (0, 30 and 60.t ha-1) on turmeric (Curcuma longa) revealed that fresh rhizome yield was significantly higher in ridge method of planting than flat method of planting with significantly taller plants and more number and weight of primary and secondary rhizomes. Farmyard manure application significantly improved plant height, number and weight of mother, primary and secondary rhizomes and fresh rhizome yield. Plant spacing did not influen~e growth and yield. Nitrogen, phosphorus and potassium contents in leaf and rhizome improved with farmyard manure application.